Impact of the West African Ebola Epidemic on Agricultural Production and Rural Welfare : Evidence from Liberia - de la Fuente, Alejandro; Jacoby, Hanan G.; Lawin, Kotchikpa Gabriel (World Bank, Washington, DC, 2019)
The 2014-15 Ebola epidemic took a devastating human and economic toll on three West African countries, of which Liberia was perhaps the hardest hit. The pathways through which the crisis affected economic activity in these largely agrarian societies remain poorly understood. To study these mechanisms in the context of rural Liberia, this paper links a geographically disaggregated indicator of Ebola disease mortality to nationally representative household survey data on agricultural production and consumption. The paper finds that higher Ebola prevalence (as proxied by local mortality) led to greater disruption of group labor mobilization for planting and harvest, thereby reducing rice area planted as well as rice yields. Household welfare, measured by per capita expenditures spanning two points before and after the crisis, fell by more in Ebola prevalent areas with more intensive rice farming, precisely those areas that were more adversely affected by agricultural labor shortages.